Proceedings of the 4th International Conference on Higher Education Advances (HEAd'18) 2018
DOI: 10.4995/head18.2018.8228
|View full text |Cite
|
Sign up to set email alerts
|

Creativity in liberal education before and after study commencement

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…It is also important to develop teaching practices and tools following the opportunities created by digitalization and emergence of artificial intelligence. Mavlutova et al [24] and Van Goch [27] emphasize that in order to stimulate entrepreneurial intentions among students, teachers should use developed practical tools like automatic digital software for assessment of business ideas of young entrepreneurs, checking of financial plans through automatic digital systems, to adapt them and to include such practices in course syllabus, thus offering better education practices.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to develop teaching practices and tools following the opportunities created by digitalization and emergence of artificial intelligence. Mavlutova et al [24] and Van Goch [27] emphasize that in order to stimulate entrepreneurial intentions among students, teachers should use developed practical tools like automatic digital software for assessment of business ideas of young entrepreneurs, checking of financial plans through automatic digital systems, to adapt them and to include such practices in course syllabus, thus offering better education practices.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested two approaches to evaluating LMS, namely evaluating the usability of the LMS and testing the effectiveness of the LMS. These factors are essential for successful and sustainable e-learning and are supported by current literature on the subject, with several authors highlighting the importance of student engagements, technical expertise, faculty engagement, faculty support of teaching and learning, infrastructure and support systems, e-learning environment and infrastructure, institutional support, didactical standards, e-learning competence of teachers, the attitude of educators, presentation and delivery of course content, course development, course structure, students' preparation, student support, continuous evaluation and revision, evaluation and assessment and role of change agents (Vovides et al, 2014;Queiros and de Villiers, 2016;Yew and Jambulingam, 2015;Bruhn-Suhr, 2004).…”
Section: Findings/discussionmentioning
confidence: 99%
“…Several other authors have written about the factors that are essential for successful and sustainable e-learning. These authors have different but similar views According to Vovides et, al (2014), Queiros and de Villiers (2016), Yew and Jambulingam (2015), and Bruhn-Suhr ( 2004) the factors essential for eLearning success includes, student engagements, Technical expertise, faculty engagement, infrastructure and support system, instructional support, students preparation, the competence of teachers, continuous evaluation and revision and the role of change agents.…”
Section: Effectiveness Of E-learningmentioning
confidence: 99%
“…As reported, these outside-class data could concern students' level of preparation, challenging parts found in the video lecture, group collaboration progress, etc. This difference is caused partly by the adoption of blended learning and the dominant format of HE lessons which has been changed from traditional lecture to face-to-face guided practice (Staker & Horn, 2012). As a result, to better support students who learn at their own pace and have differing prior knowledge, HE teachers need rich insights into learners' outside-class processes so that they could act adaptively in the classroom.…”
Section: Type Of Information and Type Of Inferencesmentioning
confidence: 99%